Estimasi Reproduction Number Model Matematika Penyebaran Malaria di Sumba Tengah, Indonesia - Banni, Ervin Mawo; Kleden, Maria A; Lobo, Maria; Ndii, Meksianis Zadrak (Jambura Journal of Biomathematics (JJBM), 2021)
Malaria is transmitted via a bite of mosquitoes and it is dangerous if it is not properly treated. Mathematical modeling can be formulated to understand the disease transmission dynamics. In this paper, a mathematical model with an awareness program has been formulated and the reproduction number has been estimated against the data from Weeluri Health Center, Mamboro District, Central Sumba. The calculation showed that the reproduction number is R0 = 1.2562. Results showed that if the efficacy of the awareness program is lower than 20%, the reproduction number is still above unity. If the efficacy of the awareness program is higher than 20%, the reproduction number is lower than unity. This implies that the efficacy of awareness programs is the key to the success of Malaria eradication.